Rural Teachers' Quality of Life Through Physical, Psychological, Social, and Environmental Lenses - Mishra, Pooja; Kumari, Pushpa (Indian Journal of Extension Education, 2025)
The paper discusses rural senior secondary school teachers' QoL. Teachers play an important role in community development by driving economic growth, social stability. The objective of the study was to evaluate the QoL of rural SSS teachers and compare it with socio-demographic factors. The study was conducted in 2022 among 185 teachers. The selection of the teachers was made through multistage sampling from Kashi Vidyapeeth and Chiraigaon block of Varanasi. The results show that age, caste, marital status, years in service, SES, family type, and education significantly impact specific QoL domains. Teachers aged >50 years reported the highest Environmental QoL scores (57.40± 20.23, p=0.001). The caste also played a role, with OBC teachers having the highest Psychological Health scores (55.78±14.71, p=0.001). Marital status was significant in Psychological Health (p=0.024) and environmental QoL (p < 0.001), with married teachers scoring higher. Teachers with >5 years in service had better Psychological Health (p = 0.026) and environmental QoL (p < 0.001). Family type also influenced QoL, with nuclear families scoring significantly higher across all domains (p < 0.05). whereas gender, religion, occupation, area of residence, and house status did not show significant differences (p > 0.05).